Methylation of Acacia auriculiformis gum polysaccharide - Singh, R.B. (Asian Journal of Chemistry, 2010)
Polysaccharide has been extracted from Acacia auriculiformis gum with water as L-arabinose and D-galactose in 1 : 4 molar ratio. Methylation of gum afforded methyl sugars as 2,3,4,6-tetra-O-methyl- D-galactose; 2,3-di-O-methyl-L-arabinose; 2,3,4-tri-O-methyl- D-galactose; 2,4-di-O-methyl-D-galactose and 2,3,4-tri-O-methyl- D-glucuronic acid in 1 : 1 : 1 : 2 : 1 molar ratio.